2015
DOI: 10.1007/s11102-015-0690-1
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of appetite and food craving in 30 patients with Cushing’s disease

Abstract: Context Glucocorticoid (GC) exposure increases food intake, but the mechanisms in humans are not known. Investigation of appetite and food craving has not been done in patients with chronic GC exposure due to Cushing’s disease (CD), either before or after treatment, and could provide insight into mechanisms of food intake and obesity in these patients. Purpose To examine whether surgical remission of CD changes appetite (prospective consumption, hunger, satisfaction, and fullness) and food cravings (sweet, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Treatment with exogenous glucocorticoids has been shown to increase food intake [48], and chronic glucocorticoid exposure has been related to increased palatable food intake[49, 50], in particular from sweet foods compared to savory foods [51]. In pathological glucocorticoid exposure, seen in Cushing’s disease, patients exhibited increased sweet craving and decreased post meal satiation [52]. Furthermore, patients with Cushing’s Disease, VAT was associated with increased post meal hunger[52], also indicating a relationship between dietary consumption cortisol and VAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with exogenous glucocorticoids has been shown to increase food intake [48], and chronic glucocorticoid exposure has been related to increased palatable food intake[49, 50], in particular from sweet foods compared to savory foods [51]. In pathological glucocorticoid exposure, seen in Cushing’s disease, patients exhibited increased sweet craving and decreased post meal satiation [52]. Furthermore, patients with Cushing’s Disease, VAT was associated with increased post meal hunger[52], also indicating a relationship between dietary consumption cortisol and VAT.…”
Section: Discussionmentioning
confidence: 99%
“…In pathological glucocorticoid exposure, seen in Cushing’s disease, patients exhibited increased sweet craving and decreased post meal satiation [52]. Furthermore, patients with Cushing’s Disease, VAT was associated with increased post meal hunger[52], also indicating a relationship between dietary consumption cortisol and VAT. The current findings may be modeling a sweet preference due to elevated cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence is inconclusive so far and especially studies regarding long‐term glucocorticoid exposure in humans are missing. One study in former CS patients revealed no change in PYY levels after remission, but unfortunately the study did not include a healthy control group 142 …”
Section: Glucocorticoids Appetite‐regulating Hormones and Eating Beha...mentioning
confidence: 98%
“…High circulating ACTH levels reduce flavor cravings, and high cortisol levels reduce postprandial satisfaction and satiety in patients with Cushing's syndrome. However, there seems to be no difference in hunger, fullness, and satisfaction between the fasting and fed conditions [118]. Fasting and postprandial circulating ghrelin levels are increased in those with Cushing's syndrome because glucocorticoids stimulate the expression of ghrelin and its receptor [119][120][121].…”
Section: Aging Stress and Feedingmentioning
confidence: 98%